Characterization of the mechanical properties and microstructural evolution of martensitic steel in repeated tempering cycles - Amitkumar Shelar; B. P. Ronge (Fracture and Structural Integrity)
The purpose of this study was to understand the behavior of martensitic H13 steel in accordance with the microstructural evolution, mechanical properties and wear in repeated tempering cycles. The microstructures were characterized by an axio image observer microscope, scanning electron microscope (SEM), and x-ray diffraction (XRD). Uniaxial tensile test, Charpy v-notch impact test, rockwell hardness test and wear test were conducted to analyze the changes in mechanical properties, impact properties, hardness and wear in repeated tempering cycles. The specimens prepared were subjected to hardening at 1030 C for 20 minutes, oil quenched and subjected to repeated tempering cycles at 570 C for 2hrs holding time each. The mechanical properties recorded indicate that the maximum ultimate tensile strength obtained was at double tempering due to secondary hardening effect i.e., alloy carbides precipitation offering strength to the matrix and corresponding wear was found to be minimum. The annealed specimen revealed bainitic microstructure and with hardening and repeated tempering cycles, fine needle like structure and carbides were observed in the microstructure and retained austenite was converted into martensite and martensite was converted into tempered martensite. Carbide size and martensite lath distribution control the strength